2008
DOI: 10.1124/dmd.108.023390
|View full text |Cite
|
Sign up to set email alerts
|

l-Methionine-dl-sulfoxide Metabolism and Toxicity in Freshly Isolated Mouse Hepatocytes: Gender Differences and Inhibition with Aminooxyacetic Acid

Abstract: ABSTRACT:L-Methionine-dl-sulfoxide (MetO) is an L-methionine (Met) metabolite, but its role in Met metabolism and toxicity is not clear. In this study, MetO uptake, metabolism to Met, cytotoxicity, and glutathione (GSH) and glutathione disulfide (GSSG) status were characterized in freshly isolated mouse hepatocytes incubated at 37°C with 0 to 30 mM MetO for 0 to 5 h. In male hepatocytes, dose-dependent cytotoxicity concomitant with GSH depletion without GSSG formation occurred after exposure to 20 or 30 mM Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 35 publications
1
20
1
2
Order By: Relevance
“…Experiments in FIMHs have provided the most recent evidence that Met SO may be enzymatically catalyzed and physiologically significant [12,13]. In one set of studies, male, but not female, FIMHs exposed only to the transaminase inhibitor AOAA showed an unexpected, time-dependent increase in cellular Met- d -O levels compared with control FIMHs (Fig.…”
Section: Methionine Metabolism: Physiological Roles and Toxicologimentioning
confidence: 99%
See 4 more Smart Citations
“…Experiments in FIMHs have provided the most recent evidence that Met SO may be enzymatically catalyzed and physiologically significant [12,13]. In one set of studies, male, but not female, FIMHs exposed only to the transaminase inhibitor AOAA showed an unexpected, time-dependent increase in cellular Met- d -O levels compared with control FIMHs (Fig.…”
Section: Methionine Metabolism: Physiological Roles and Toxicologimentioning
confidence: 99%
“…In one set of studies, male, but not female, FIMHs exposed only to the transaminase inhibitor AOAA showed an unexpected, time-dependent increase in cellular Met- d -O levels compared with control FIMHs (Fig. 5) [12]. This result led to the identification of methionine- dl -sulphoxide (MetO) TA as a novel metabolic pathway of interest and suggested that Met S -oxidation and MetO TA may occur in vivo at physiological Met concentrations and have some unidentified physiological role.…”
Section: Methionine Metabolism: Physiological Roles and Toxicologimentioning
confidence: 99%
See 3 more Smart Citations